Twilight in Delhi - Ahmed Ali (New Delhi Rupa Publications India (Pvt.) Ltd., 2007)
Set in nineteenth-century India between two revolutionary moments of change, Twilight in Delhi brings history alive, depicting most movingly the loss of an entire culture and way of life. As Bonamy Dobree said, "It releases us into a different and quite complete world. Mr. Ahmed Ali makes us hear and smell Delhi...hear the flutter of pigeons$1 (Bwings, the cries of itinerant vendors, the calls to prayer, the howls of mourners, the chants of qawwals, smell jasmine and sewage, frying ghee and burning wood." The detail, as E.M. Forster said, is "new and fascinating," poetic and brutal, delightful and callous. First published by the Hogarth Press in 1940. Twilight in Delhi was widely acclaimed by critics and hailed in India as a major literary event. Long since considered a landmark novel, it is now available in the U.S. as a New Directions Classic. Twilight in Delhi has also been translated into French, German, Portuguese, Spanish, and Urdu.s
A Novel
Keywords: India--Delhi -- Muslims -- Domestic fiction -- Families